PERBANDINGAN PEKERJAAN ARSITEKTUR ANTARA RAB PROYEK DENGAN BIM CUBICOST PADA GEDUNG LABORATORIUM ISI SURAKARTA - S, Canggih Gilang Pradana H.; Vitria, Arda Haffizha Putri; Fahrudin, Deva Muhammad (Prodi Teknik Sipil Fakultas Teknik Universitas Sebelas Maret Surakarta, 2025)
Engineers increasingly use project management technology such as Building Information Modelling (BIM) to optimize resource utilization and minimize costs in construction projects. Cubicost is a 5D BIM software used for volume and material price calculations. This research aims to compare architectural work volumes using Cubicost Takeoff for Architecture and Structure (TAS) with contractor volumes and conduct a comparison analysis of the Budget Plan (RAB). This study employs a quantitative method through a simple linear regression approach to validate Cubicost results with the author's manual calculations. First, data is collected to be modeled using Cubicost software. Then, a simple linear regression analysis is conducted to assess the validity of Cubicost based on the author's manual calculations. Next, a comparison of volumes and RAB between Cubicost results and contractors is performed to analyze deviations caused by contractor human error factors and determine the percentage of efficiency in Cubicost software usage. The comparison of Cubicost with the contractor results in a cost efficiency of Rp734,925,053.97 or an efficiency percentage of 18.429%. Based on these results, this research recommends the implementation of Cubicost in the construction project of the Integrated Multi-Matra SBSN ISI Surakarta Laboratory Building for decrease human error in this project.